2023
DOI: 10.3390/ijms241814358
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Role of Vasopressin/Oxytocin-Type Neuropeptide in Osmoregulation and Feeding Inhibition of Apostichopus japonicus

Xiao Cong,
Huachen Liu,
Yingqiu Zheng
et al.

Abstract: Vasopressin/oxytocin (VP/OT)-type neuropeptide is an ancient neurophysin-associated neuropeptide and has been intensively studied to be involved in multiple physiological processes in protostomian and deuterostome vertebrates. However, little is known about the functions of VP/OT-type neuropeptide in deuterostome invertebrates especially in echinoderms. Here, we firstly report VP/OT-type neuropeptide signaling in an important economic species, Apostichopus japonicus, which is widely cultured in Asia, with high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…In A. japonicus, we found that the vasopressin/oxytocin-type neuropeptide (VP/OT) has a strong contractile effect on a variety of muscle tissues, including LMBW, intestinal muscle, and tentacles. Ca 2+ deprivation experiments have shown that VP/OT-induced contraction is dependent on extracellular Ca 2+ influx [150]. However, the channel that mediates Ca 2+ influx and the intracellular signaling pathway that activates it are still unknown.…”
Section: Neuropeptidesmentioning
confidence: 99%
“…In A. japonicus, we found that the vasopressin/oxytocin-type neuropeptide (VP/OT) has a strong contractile effect on a variety of muscle tissues, including LMBW, intestinal muscle, and tentacles. Ca 2+ deprivation experiments have shown that VP/OT-induced contraction is dependent on extracellular Ca 2+ influx [150]. However, the channel that mediates Ca 2+ influx and the intracellular signaling pathway that activates it are still unknown.…”
Section: Neuropeptidesmentioning
confidence: 99%